Making a Difference: University Students of Color Speak Out - Lesage, Julia; Ferber, Abby L.; Storrs, Debbie; Wong, Donna (Rowman & Littlefield Publishers, 2002)
Students of color relate their first-hand experiences with educational systems and campus living conditions. Their narratives provide an insider perspective useful to anyone working on diversity issues who is trying to improve institutional culture and policy. The book is a user-friendly guide. The first section focuses on the voices of students of color and draws on the power of personal narratives to reveal alternate perspectives that illuminate and contest the dominant cultures often hidden beliefs about race, culture, institutional goals and power. Following the narratives, contextualizing essays and a lengthy appendix provide further valuable resources and concrete tools, such as websites, lists of associations, a bibliography, and videography of autobiographical videos by people of color. This book should be read by faculty members and students (both white and non-white), parents of college students, college administrators, and executives and administrators of other institutions and businesses. The contextualizing essays following the student narratives are written by academics and student affairs professionals who draw links between issues of institutional access, recruitment and retention of students and faculty of color, curriculum changes, teaching strategies—especially for teaching whiteness and racial identity formation, campus climate, and the relation between an individual institution's history of dealing with race to developments in public policy.